2019
DOI: 10.1007/s00216-019-02171-9
|View full text |Cite
|
Sign up to set email alerts
|

Chemical profiles of birch and alder bark by ambient mass spectrometry

Abstract: Desorption atmospheric pressure photoionization (DAPPI) is an ambient mass spectrometry (MS) technique that allows the analysis of both polar and nonpolar compounds directly from the surfaces of various sample types. Here, DAPPI was used to study the chemical profiles in different parts of birch and alder tree barks. Four distinct fractions of Betula pendula (silver birch) bark were collected from three different developmental stages of the stem, after which the chemical profiles of the different tissue types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…34,35 Recently, two different OPO IR laser-beam-focus-ing techniques 36,37 have been reported that allow IR laser-ablation MSI with even 50-µm spatial resolution. Thus far, LAAPPI has been demonstrated in MSI of mouse brain, 36 whole sage leaves, 23 and birch bark 38 with 60-µm, 400-µm, and 400-µm spatial resolutions, respectively. On the other hand, LAESI has been widely used in MSI, such as in the analysis of whole rat brain, 30 bacterial colonies, 31 and A. squarrosa leaves.…”
mentioning
confidence: 99%
“…34,35 Recently, two different OPO IR laser-beam-focus-ing techniques 36,37 have been reported that allow IR laser-ablation MSI with even 50-µm spatial resolution. Thus far, LAAPPI has been demonstrated in MSI of mouse brain, 36 whole sage leaves, 23 and birch bark 38 with 60-µm, 400-µm, and 400-µm spatial resolutions, respectively. On the other hand, LAESI has been widely used in MSI, such as in the analysis of whole rat brain, 30 bacterial colonies, 31 and A. squarrosa leaves.…”
mentioning
confidence: 99%
“…There are many other plant species that produce betulin ( 8 ) in low amounts, but to the best of our knowledge, none of them are used as important sources of it. Lupeol ( 9 ) is another lupane triterpene naturally occurring in plants; however, its quantities are usually lower than the quantities of 5 or 8, and it is usually obtained as a side-product of extractions of other triterpenes [ 49 , 50 , 51 ]. A basic summary of the main lupane triterpenoid sources is in Table 1 .…”
Section: Natural Sources Of Betulinic Acid (5) Betulin (8) and Lupeol (9)mentioning
confidence: 99%
“… Methods of synthesis of betulinic acid [ 47 , 48 , 49 , 50 , 51 , 52 ]. Reagents and conditions: (i) chromium(VI) oxide; sulfuric acid, and acetone, H 2 O; (ii) sodium tetrahydroborate and isopropyl alcohol; (iii) 4-acetylamino-2,2,6,6-tetramethylpiperidine-N-oxyl, sodium chlorite, tetrabutylammomium bromide, sodium hypochlorite, and phosphate buffer at 50 °C; (iv) 4-acetylamino-2,2,6,6-tetramethylpiperidine-N-oxyl, tetrabutylammomium bromide, sodium hypochlorite, and phosphate buffer (pH = 7.6) at 50 °C; (v) BAIB, TEMPO, NaH 2 PO 4 , NaClO 2 , 2-methyl-2-butene, BuOAc, water, and t-BuOH at 20 °C for 6 h; (vi) 2,6,6-tetramethyl piperidine-N-oxyl, tetrabutylammomium bromide, and sodium hypochlorite in phosphate buffer with dichloromethane for 6 h with pH = 6.8; (vii) sodium dihydrogenphosphate, sodium permanganate, DCM, water, and tert-butyl alcohol at 25 °C for 3 h; (viii) K 2 CO 3 and MeOH for 24 h; and (ix) KOH and MeOH with heating for 3 h. …”
Section: Figures Schemes and Tablesmentioning
confidence: 99%
“…Modern spectroscopic methods have been explored for structural elucidation of bioactive constituents present in weeds. LC-MS has been used for quantitative detection of xyloglucan oligosaccharide in Selaginella kraussiana [11], betulonic acid in Alnus glutinosa (Black alder) [12], jasmonic acid in Drosera capensis (Cape sundew) [20], lavonoids in Gunnera tinctoria (Chilean rhubarb) [24], pyrrolizidine alkaloid esters in Gymnocoronis spilanthoides (Senegal tea) https://doi.org/10.29328/journal.jpsp.1001050 [42]. NMR employed for characterization of compounds present in Fraxinus excelsior (Ash) [15], Berberis glaucocarpa (Barberry) [17], Ligustrum sinense (Chinese privet) [25], Rhamnus alaternus [26], Cestrum parqui (Green cestrum) [30], Ranunculus sardous (Hairy buttercup) [49].…”
Section: Chemical Profi Le Of Weeds Established In New Zealandmentioning
confidence: 99%